A gestão democrática e a educação de jovens e adultos no Plano Municipal de Educação de João Pessoa (2015-2025): correlatos enunciativos - Rodrigues, Krislânia Damascena (2021)
Democratic management and Youth and Adult Education (EJA) are present in the legal provisions that regulate the Brazilian education, such as the Federal Constitution of 1988 and LDB 9.394/96. Are themes widely discussed at the political, pedagogical and academic levels. In order to analyze the issue, this work had for object of research the enunciative correlations between democratic management and EJA in the Municipal Education Plan of João Pessoa (2015-2025). We have a theoretical dialogue with Ferreira and Rodrigues (2016) and Volpe (2004) about EJA, and with Gadotti (2013, 2014) and Paro (2010, 2012) on educational management. The work sought theoretical and methodological foundations in Alcantara and Carlos (2013) and Foucault (2008) to organize the analytical procedures and operate with the notions of discourse and utterance. The analysis was based on the excavation of the documental network that circumscribes the correlates of democratic management and EJA in the Municipal Education Plan/JP. The results of analysis show that the articulating correlates of democratic management and EJA are the following signs enunciative: knowledge, the political-pedagogical field and the subjects of the public school. Therefore, management democracy and EJA appear in the Municipal Education Plan/JP articulated to a discursive network that affirms the public education as a universal right, a basic prerequisite for building citizenship.